UNIVERSITY WRITING CENTERS IN RUSSIA: GOALS AND PROSPECTS - Irina B. Korotkina (Высшее образование в России, 2016)
The author gives an overview of the first few academic writing centers in Russian universities and compares their missions and functions in terms of target audience and outcomes for the universities. She concludes that writing centers in Russia will currently develop with the aim of providing help for faculty in publishing their papers in international academic journals rather than helping students with their academic writing. Students' writing should remain the responsibility of university language programs, which need considerable improvement and involve academic writing methodology. The future of writing centers is viewed as a tool in overcoming disciplinary and institutional borders and leading to the internationalization of Russian higher education. The author recommends that both academic writing and writing for publication should be delivered in both English and Russian, thus covering a much wider audience of students and faculty.